Pengaruh Kepercayaan Diri terhadap Motivasi Belajar Mahasiswa PAI pada Mata Kuliah Materi Pembelajaran Aqidah Akhlak - Fitri Khairun Nisa; Syamsuri Ali; Erni Yusnita (MAN 4 Kota Pekanbaru, 2026)
The present research seeks to analyze the significance of self-confidence in shaping the learning motivation of Islamic Religous Education (IRE) students in the Aqidah Akhlak course at the State Islamic University of Raden Intan Lampung. The study was conducted among IRE students from the 2023 cohort who were enrolled during the first term of the 2025–2026 academic period. The study population consisted of comprised IRE students. from classes A to K, totaling 349 individuals. The results show that greater degrees of self-confidence are connected to improved learning motivation, greater student engagement in the learning process, and improved academic achievement. This is evidenced by a positive regression coefficient of 0.731, along with significant t-test and F-test results at the 95% confidence level. These findings confirm that self-confidence is a crucial factor in enhancing the learning motivation of IRE students.